The Position of Geography in Secondary School Curricula: A Comparative Analysis of Indonesia’s Merdeka Curriculum and Malaysia’s KSSM - Fauzan Asyim; Dedi Hermon; Febriandi Febriandi (AL-ISHLAH: Jurnal Pendidikan, 2026)
This study examines the position and strategic status of Geography as a secondary school subject in Indonesia and Malaysia, focusing on its compulsory or elective placement, curriculum depth, and contribution to students’ geopolitical understanding. The research aims to highlight the novelty of subject positioning analysis rather than pedagogy alone, addressing how curricular structures shape geopolitical literacy outcomes. Employing a qualitative descriptive comparative design, the study integrates curriculum document analysis, semi-structured stakeholder interviews, and SWOT analysis to identify similarities, differences, strengths, and challenges in both education systems. Data sources include Indonesia’s Merdeka Curriculum and Malaysia’s Kurikulum Standard Sekolah Menengah (KSSM), supported by relevant literature and educator perspectives. Key findings show that Geography holds a strategic role in both countries by fostering spatial and geospatial literacy, regional awareness, and understanding of national and global issues, yet its positioning differs: Indonesia emphasizes Geography within social science specialization with stronger geopolitical orientation, while Malaysia introduces it at lower secondary but shifts it to an elective subject at upper secondary with broader environmental and development themes. The study implies that strengthening Geography’s geopolitical contribution requires clearer curriculum integration, sustained subject continuity, enhanced teacher professional development, and wider use of geospatial technologies to better equip students for contemporary geopolitical challenges.